FACTORS ASSOCIATED WITH THE INCIDENCE OF PRURITUS VULVAE IN ADOLESCENTS: A LITERATURE REVIEW - Zahra, Haffizha Aulia; Adyani, Kartika (Journal of Maternity Care and Reproductive Health, 2025)
A common menstrual disorder among adolescents is vulvar pruritus. The exact prevalence of vulvar pruritus is unknown, but previous studies have demonstrated that this occurrence is triggered by various factors. The focus of this study is to describe factors associated with the manifestation of vulvar pruritus in adolescents. The method used is article review by searching the Google Scholar and PubMed databases, combining the keywords "vulvar pruritus," "genital itch," "hygiene," "menstruation," and "reproductive health”. Criteria for articles published in the years 2019-2024 from reputable journals, available in full text and accessible, as well as researching factors related to vulvar pruritus or its symptoms. Research with non-adolescent samples and articles in the form of theses/repositories/case reports are excluded. A total of 74 articles were obtained and subsequently selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. The selected 9 articles were analyzed by reading thoroughly and extracting relevant information. The analysis of the article indicated that the factors significantly related to the occurrence of vulvar pruritus in adolescents are knowledge about hygiene during menstruation and hygiene practices during menstruation. In the conclusion, the most influential factor is hygiene behavior during menstruation. Further studies are expected to expand the scope of other risk factors that may also have a correlation with the manifestation of vulvar pruritus in adolescents.